2017
DOI: 10.3389/fpsyg.2017.01042
|View full text |Cite
|
Sign up to set email alerts
|

Utilitarian Moral Judgment Exclusively Coheres with Inference from Is to Ought

Abstract: Faced with moral choice, people either judge according to pre-existing obligations (deontological judgment), or by taking into account the consequences of their actions (utilitarian judgment). We propose that the latter coheres with a more general cognitive mechanism – deontic introduction, the tendency to infer normative (‘deontic’) conclusions from descriptive premises (is-ought inference). Participants were presented with vignettes that allowed either deontological or utilitarian choice, and asked to draw a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…Fundamentally, all these initiatives expose tensions between societal vs individual interests . Interestingly, testing of the role of deontic introduction in moral inference found that the tendency to infer normative conclusions mostly coheres with utilitarian (rather than deontological) judgments, which can explain increasing outrage over ever‐increasing health care costs …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fundamentally, all these initiatives expose tensions between societal vs individual interests . Interestingly, testing of the role of deontic introduction in moral inference found that the tendency to infer normative conclusions mostly coheres with utilitarian (rather than deontological) judgments, which can explain increasing outrage over ever‐increasing health care costs …”
Section: Discussionmentioning
confidence: 99%
“…92 Fundamentally, all these initiatives expose tensions between societal vs individual interests. 73 Interestingly, testing of the role of deontic introduction in moral inference found that the tendency to infer normative conclusions mostly coheres with utilitarian (rather than deontological) judgments, 86 which can explain increasing outrage over ever-increasing health care costs. 93 Another example of a goal conflict, one that all too often leads to "overtreatment" with aggressive therapy rather than a more appropriate palliative approach such as hospice, is the end-of-life setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual reality presentation of moral dilemmas will have more ecological validity, and will be better in predicting individuals’ behaviors ( Patil et al, 2014 ). Finally, Elqayam et al (2015 , 2017 ) proposed a processing model for deontic introduction to explain the process of moral judgment, and found deontic introduction was only related to utilitarian moral judgment. It would be interesting to explore the role of deontic introduction in the association between emotion regulation difficulties and moral judgment.…”
Section: Discussionmentioning
confidence: 99%
“…Participants face two options: to hit a switch to divert the trolley to another track, and to save the five workmen at the cost of the death of one workman on that track, or to do nothing, and to let the trolley cause the deaths of the five workmen ( Greene et al, 2004 ). The preference for the former is regarded as a utilitarian judgment ( Mill, 1861/1998 ), judging mainly on the basis of the consequences of the actions ( Elqayam et al, 2017 ), and the preference for the latter is interpreted as a deontological judgment ( Kant, 1785/1959 ), judging mainly on the basis of pre-existing obligations ( Elqayam et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%